Screening for phaeochromocytoma and paraganglioma: impact of using supine reference intervals for plasma metanephrines with samples collected from fasted/seated patients. (January 2017) - Casey, R; Griffin, TP; Wall, D; Dennedy, MC; Bell, M; O'Shea, PM
Background: The Endocrine Society Clinical Practice Guideline on Phaeochomocytoma and Paraganglioma recommends phlebotomy for plasma-free metanephrines with patients fasted and supine using appropriately defined reference intervals. Studies have shown higher diagnostic sensitivities using these criteria. Further, with seated-sampling protocols, for result interpretation, reference intervals that do not compromise diagnostic sensitivity should be employed. Objective: To determine the impact on diagnostic performance and financial cost of using supine reference intervals for result interpretation with our current plasma-free metanephrines fasted/seated-sampling protocol. Methods: We conducted a retrospective cohort study of patients who underwent screening for PPGL using plasma-free metanephrines from 2009 to 2014 at Galway University Hospitals. Plasma-free metanephrines were measured using liquid chromatography-tandem mass spectrometry. Supine thresholds for plasma normetanephrine and metanephrine set at 610 pmol/L and 310 pmol/L, respectively, were used. Results: A total of 183 patients were evaluated. Mean age of participants was 53.4 (±16.3) years. Five of 183 (2.7%) patients had histologically confirmed PPGL (males, n =4). Using seated reference intervals for plasma-free metanephrines, diagnostic sensitivity and specificity were 100% and 98.9%, respectively, with two false-positive cases. Application of reference intervals established in subjects supine and fasted to this cohort gave diagnostic sensitivity of 100% with specificity of 74.7%. Financial analysis of each pretesting strategy demonstrated cost-equivalence (€147.27/patient). Conclusion: Our cost analysis, together with the evidence that fasted/supine-sampling for plasma-free metanephrines, offers more reliable exclusion of PPGL mandates changing our current practice. This study highlights the important advantages of standardized diagnostic protocols for plasma-free metanephrines to ensure the highest diagnostic accuracy for investigation of PPGL.